Notes on current Mbyá-Guarani medicinal plant exchanges in southern Brazil - Julian Henrique Carlotto de Andrade; José Rodrigues; André Benites; Cornélio Benites; Arlindo Acosta; Marcelina Benites; Cocelina Benites; Ilda Gomes; Jaime Valdir da Silva; Eunice Antunes; Elisete Antunes; José Martins; et al. (BMC, 2021)
Abstract Background Experts in the Atlantic Forest, the Guarani people have the habit of transporting and exchanging plants due to their mobility throughout the territory. Historically, this habit contributed to the species composition and diversification among different phytophysiognomies that comprise the Atlantic Forest. Medicine and spirituality are traits that stand out within the Guarani culture, which is based on a holistic understanding of physical and spiritual well-being for the person's health. To achieve this balance, they use a range of native and adapted plant species. Our goal is to understand some of the Guarani contributions to the cultural landscape in the Atlantic Forest. Methods We conducted semi-structured interviews with key persons asking about the importance of forest environments for Guarani health and about visits to other Guarani villages and plants exchanged. Data analysis was qualitative, and through a bipartite network of exchanged plants to show current plant exchanges between villages. Results We visited seven Guarani Indigenous Territories in south Brazil, and with the participation of 12 respondents, we registered 27 species that were exchanged through different phytophysiognomies in the Atlantic Forest. These results show an intense movement of plants currently occurring between villages and the importance of these movements for both individual health and the integrity of the environments in which the Guarani villages are inserted. Conclusions We observed a search for the maintenance of traditional species in the Guarani medical system, and we highlight the fundamental role of Guarani management in the conservation of the southern Atlantic Forest in indigenous territories.